2014
DOI: 10.1039/c4ra11457d
|View full text |Cite
|
Sign up to set email alerts
|

TiO2nanotubes with tunable morphologies

Abstract: Titanium anodic oxide layers with a bottle shaped nanotubular structure have been grown in an electrolyte containing NH 4 F, applying voltage steps. The grown layers were analyzed using scanning and transmission electron microscopy (SEM and TEM), and Rutherford backscattering spectroscopy (RBS). The results show that a concentration of 0.15 M of NH 4 F in the anodizing bath, and a step of 10 to 20 V produces an oxide with a double morphology comprised of nanotubes at the oxide/metal interface and nanopores at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…Bottle‐shaped TiO 2 nanotubes (bNT) were prepared in an electrolyte containing 1 M NH 4 H 2 PO 4 and 0.3 M NH 4 F and applying two‐stepped voltage: a first voltage step of 10 V for 30 min, followed by the second step of 20 V for 60 min …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bottle‐shaped TiO 2 nanotubes (bNT) were prepared in an electrolyte containing 1 M NH 4 H 2 PO 4 and 0.3 M NH 4 F and applying two‐stepped voltage: a first voltage step of 10 V for 30 min, followed by the second step of 20 V for 60 min …”
Section: Methodsmentioning
confidence: 99%
“…Bottle-shaped TiO 2 nanotubes (bNT) were prepared in an electrolyte containing 1 M NH 4 H 2 PO 4 and 0.3 M NH 4 F and applying two-stepped voltage: a first voltage step of 10 V for 30 min, followed by the second step of 20 V for 60 min. 12 Antibiotic load and release from bNT Antibiotic load and release from bNT were evaluated using the methodology previously described by Aguilera-Correa et al, 16 where GV (Sigma-Aldrich, St. Louis, MO) were loaded into bNT layers by the method described by Doadrio et al 15 In brief, the load of the mixture of GV were prepared with 75 mg of each antibiotic in 20 ml of water. For the loading, the specimens were held by a platinum wire and introduced in a polypropylene recipient containing 20 ml of the antibiotic aqueous solution under continuous stirring, for 24 h to reach the maximum drug adsorption.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pH values were adjusted to 4.4-4.6 using NaOH and measured using narrow range (4.0-7.0) pH indicator strip (Whatman). Finally, bottle shaped nanotubes (NTb) were formed in the same electrolyte than previous applying two stepped voltage: a first voltage step of 10V for 30 min, followed by a second voltage step of 20V for 60 min (Hernández-López et al, 2014).…”
Section: Sample Preparationmentioning
confidence: 99%
“…It was found that the electrochemical anodization in fluoride-containing electrolytes is the simplest and the low cost technique that was employed extensively to synthesis nanoporous and nanotubular TiO2 thin films on titanium and Ti-based surface alloys [21].…”
Section: Introductionmentioning
confidence: 99%